Uma contribuição ao estudo dos campos eletromagnéticos gerados por descargas atmosféricas - Evandro Jose Ribeiro (2005)
This work presents a contribution to the electromagnetic fields study due lightning through computational simulation and measurements in reduced model. Equations in cartesian coordinates to calculate electromagnetic fields due arbitrary sources in the time domain were obtained via electric dipole method. These equations were studied and simplified for the calculation of fields due current transitory in horizontal and vertical conductors. Investigations about field regions for impulsive signals and influences of the lightning channel size, the lightning channel losses and the return stroke waveform in the electromagnetic fields in regions of near field were carried out. Models in reduced scale were implemented, as well as simple and cheap electromagnetic field measurement system. The electromagnetic fields in reduced scale were measured and compared with simulation generating credibility of the results. An example of application of the model reduced in the study of electromagnetic shield is presented.